The Effect of Elastic Resistance Band Training on Developing Muscular Power and Reactive Agility in Under-18 Basketball Players - Mohammed Ali, Dhulfiqar Fadhil; Smoom, ٍHussein Jasim; Abdulhussein, Ahmed Amer (Journal of Physical Education, 2026)
The study aimed to identify the effect of elastic resistance band training on developing lower- and upper-limb muscular power and reactive agility among under-18 basketball players. The experimental method was used with a pre- and post-test design for two equivalent groups (experimental and control). Twelve Al-Defaa Al-Jawiy volleyball players were randomly assigned into two groups of six individuals. The experimental group underwent an 8-week training program using elastic resistance bands, with a frequency of three times per week, independent of the traditional intervention applied to the control group. Strength of the lower-limb musculature was assessed by vertical jumping, strength of the upper-limb musculature by medicine ball throwing and reactive agility using visual reaction time testing. The post-test results showed statistically significant differences that favored the experimental group in all research variables and exhibited a tendency of muscular power and reactive agility improvements when compared with the control group. It was founding that elastic resistance band training can be an effective and safe way to develop these physical abilities associated with skill performance in youth basketball due to its generation of the progressive resistance, which contributes to the neuromuscular benefits and movement efficiency.